Effect of the protein level in maize silage-based diets on performance of early weaned lambs’ fattening and carcass characteristics - Benassou L.; Chicha S.; Mounsif M.; Benbati M.; Mokhtari N.; Keli A. (Efficiency and resilience of forage resources and small ruminant production to cope with global challenges in Mediterranean areas, 2021)
The aim of this study was to evaluate effects of different protein levels in maize silage-based diets on weaned lambs performance and carcass characteristics. Sixty Moroccan (local breed) early weaned lambs (14.7±0.45 kg initial body weight and 80±6.3 days were divided into three treatments, 20 males each. They received a diet containing maize silage (21%), wheat straw (19%) and concentrate supplement (60% as dry matter basis) with different protein levels, 18 (T1), 16 (T2) and 14 (T3) g crude protein/ 100 g dry matter of the supplement. The trial lasted for 105 days after 14-day of adaptation period. Feed offered and orts were daily registered and feed intake calculated. Lambs were weighed at the beginning and at the end of the trial, and fortnightly in order to determine the average daily gain and feed conversion. At the end of the trial, 3 lambs per each treatment were slaughtered. The carcass dressing percentage, fatness (1-5 scale) and conformation (SEUROP system) were determined. Results revealed that the protein level did not affect either lamb fattening performance or carcass characteristics for the whole period. The ADG was 223.3, 193.9 and 205.4 g/ day for T1, T2 and T3, respectively. Feed conversion ratio was 4.7, 5.6 and 5.5 kg dry matter intake/ kg ADG for T1, T2 and T3, respectively. The dressing percentage and fatness were 56.5, 54.1 and 55.1% and 2.8, 2.3 and 2.5 for T1, T2 and T3, respectively. In conclusion, lambs may be fed maize silage-based diets containing 20 % of maize silage and concentrate feed supplement containing 14% CP during the fattening period without negative effects on lambs performance and carcass characteristics.
1. Joint meeting of the FAO-CIHEAM Networks on Sheep and Goats (Subnetworks on Nutrition and Production Systems) and on Mediterranean Pastures, 2019/10/23-25, Meknes (Morocco)